Addicted to love - Gordon, Robert; Silver, Jeffrey; Newmyer, Bobby 1956-2005; Dunne, Griffin 1955- (Warner Home Video, 1997)
What would you do if that special someone dumped you? If you're like Maggie or Sam, the better question is what wouldn't you do! They play Maggie and Sam, teaming for revenge when their exes team for romance. At first, Sam simply wants his girlfriend back. Maggie wants to get back at her old flame. So in the parks, lofts and trendy eateries of New York's Soho, they